Food patterns and chronic obstructive pulmonary disease in the SAPALDIA cohort - Steinemann, Nina; Justus Liebig University Giessen (My University, 2019)
Worldwide, the prevalence of chronic obstructive pulmonary disease (COPD) is dramatically increasing. COPD will account for the third leading cause of death by 2020, thus representing a major public health issue. COPD is not restricted to smokers and dietary habits may contribute to the disease occurrence. Epidemiological research points to a benefit of a diet rich in antioxidants and omega-3 fatty acids for protecting from loss of lung function and from COPD symptoms, and protective effects of fruit and vegetable intake have been shown in several cohort studies. The aims of the current study were to derive and analyze dietary patterns for Swiss adults and to assess their association with lung function and COPD in the Swiss Cohort Study on Air Pollution and Lung and Heart Diseases in Adults (SAPALDIA). Dietary intake was collected using a paper form food frequency questionnaire (FFQ) designed to assess average food intake over the previous 4 weeks (www.ernaehrungserhebung.ch). In order to apply a robust and reliable tool, the FFQ had to be validated first. The FFQ validation study therefore presents the precondition study for the main research questions in the context of food patterns and COPD in the SAPALDIA cohort. The study aimed at assessing the relative validity of a paper form FFQ with a 4-day FR. The validity was assessed both, at the energy and macronutrient and food group levels. Finally, data from 56 out of a total of 60 recruited participants were considered for the analysis. In conclusion, the 127-food item FFQ showed good relative validity for protein and various, commonly consumed food groups such as fruits, egg, meat, sausage, nuts, salty snacks and beverages. The applied FFQ was shown to be an appropriate tool for assessing and characterizing dietary intake and food habits of adults in epidemiological studies.For the main analysis, 2178 SAPALDIA participants with complete data on lung function, smoking history, physical activity and dietary intake were considered. The validated, semi-quantitative paper form FFQ was handed out to the study participants and filled in self- administered. To derive dietary patterns, principal component factor analysis was performed on 25 predefined food groups on the basis of similarity of type of food and nutrient composition. Three prominent food factors were identified: Factor 1 reflected a rather healthy diet , i.e. a prudent pattern , characterized by the main food groups vegetables, fruits, water, tea and coffee, fish and nuts. In contrast, factor 2 was described by a high intake of meat, sausage, egg, fish and alcohol, representing a rather unhealthy diet , i.e. a traditional Western pattern . In addition, a third factor was identified, which was characterized by a high-carbohydrate diet , i.e. a high intake of sweet spreads, bread, dessert and potatoes. In order to analyze the relationships between dietary patterns and lung function outcomes and COPD, multiple mixed linear and logistic regression models were applied. The main finding was the positive association of the prudent pattern with the lung function parameter FEV1. These results are in line with current literature on dietary patterns and lung function outcomes or COPD. Thus, our results also add to the general evidence of a protective effect of antioxidant intake in COPD. For COPD prevention, smoking cessation still presents the most relevant public health message. However, the results of the present study suggest diet as a modifiable potential risk factor of lung function decrease. The investigation of dietary patterns rather than single food items or nutrients has the advantage of addressing the influence of food habits in their lifestyle context; it therefore better captures the complex nature of diet. In addition to the nutritional guidelines for other NCDs (e.g. cardiovascular diseases, diabetes, cancer), recommendations for high fruit and vegetable intake and low meat and alcohol intake may become an important pillar of respiratory disease prevention. The present study design and methodical approach could be transferred to other studies analyzing the relationship of diet and a specific disease such as other NCDs (e.g. cardiovascular diseases). In order to elaborate national nutrition strategies and concrete recommendations, there is a need for epidemiological research as it presents a precondition for a solid data basis. In addition, the novelty of these results for Switzerland must be considered. Since there are currently no other data about the relationship between dietary patterns and COPD in Switzerland, the findings of the present study are crucial. They point out important results of a potential beneficial effect of a rather healthy diet in comparison to a rather unhealthy diet regarding the occurrence of COPD.
Keywords: ddc:610